Macroeconomic Determinant Variables In LQ45 Retail and Consumer Goods Securities Performance Index. - Septina, F. (Review of Management and Entrepreneurship, 2017)
The research aimed to examine the changes of macroeconomic variables which affected securities performance in retail and consumer goods industry. Investors who wanted to get return in the short-run and long-run from thwassecurities should concern the economic circumtances too, besides other systematic risks. Those industries produced consumer goods and gave direct impacts to the market. Securities performance was proxied by the return of securities. Macroeconomics variables were proxied by return LQ45 Index, consumer price index (IHK–Indeks Harga Konsumen), inflation rates, Gross Domestic Product (GDP), interest rates (BI Rate), and exchange rates of Indonesian Rupiah to US Dollar. Samples werewere monthly securities trading LQ45 Index of retail and consumer goods firms from January 2014 to July 2016, also the macroeconomic data from Bank of Indonesia. The data taken were assumed during the period of Joko Widodo’s presidency. The research methods were multifactor regressions and correlation.